KOMUNIKASI INTERPERSONAL PETUGAS PUBLIC RELATION DALAM MEMBANGUN HUBUNGAN DENGAN MEDIA - Darmadi, Darmadi (Liwaul Dakwah: Jurnal Kajian Dakwah dan Masyarakat Islam, 2021)
The duties and functions of public relations officers will run well if they are carried out responsibly. Since this duties concerns with other people, so it requires a good understanding of communication. It is especially true in building relationships between public relations officers and media workers. It takes special skills to be able to understand the duties and functions of each. Therefore, interpersonal communication will provide opportunities for all parties to understand each other so that they can carry out their responsibilities. The personal closeness between public relations officers and media workers will determine the quality of communication between them which will affect the results. In this regard, the success of the duties of a public relations officer will be determined by their ability to build interpersonal communication with various groups.